Strategies of resistance and empowerment of portuguese women coaches in sports - Ludmila Mourão; Paula Silva; Silvana Vilodre Goellner; Paula Botelho Gomes (Revista da Educação Física)
The participation of women in sports is the subject of analysis of several studies that continuously evidence inequality and asymmetry in relation to men in the different spheres of activity within this field. The objective of this study is to comprehend male hegemony as coaches and how it is accepted and/or contested in the sports environment by identifying attitudes that incorporate this male dominance or that contradict and resist it. The sample of this study is composed of interviews with 37 Portuguese female coaches in both individual and team sports. The results indicate that the presence of women in leadership positions in sports, such as of head coach, does not ensure in itself an objection to male hegemony. It becomes necessary that women incorporate the concept of “agency” in order to identify and implement strategies that resist and consequently change the patriarchal structures that perpetuate the underrepresentation of women in coaching sports.